Implementation of Equivalence Partitioning and Boundary Value Analysis in Black Box Testing A Case Study on the Admin Website of PAUD KB Al Husna - Adelia Tiara Putri; Aisya Arline Husnaya; Dzaky Fachri Hadafi; Hasan Ismail Abdulmalik; Muhammad Nasir; Sofiyanti Indriasari (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In order to guarantee system functioning and quality, software testing is an essential stage in the Software Development Life Cycle (SDLC). This study implements black box testing using Equivalency Partitioning (EP) and Boundary Value Analysis (BVA) on the Admin Website PAUD KB Al Husna to identify functional defects, focusing on input validation and error handling. In this study, 82 test scenarios were created for five functional modules (Class Management, Teacher Management, FAQ, Schedule, Gallery) and three non-functional factors (Security, Compatibility, and Responsiveness). Test execution was conducted manually based on BVA test cases (Min-1, Min, Max, Max+1) and EP cases (valid and invalid classes). Results showed a 32.9% failure rate (27 of 82 scenarios). Critical findings include: (1) Systemic failure in upper-boundary validation (BVA Max+1) with 256-character inputs; (2) EP-Invalid validation failures revealing Cross-Site Scripting (XSS) vulnerabilities from HTML input; and (3) Absence of brute-force protection on login pages. The study concludes that BVA and EP techniques effectively identify critical data validation and security defects, providing essential improvement recommendations for developers.